Model Dakwah bi al-Irsyãd untuk Pemeliharaan Kesehatan Mental Spiritual Pasien di Rumah Sakit - Isep Zaenal Arifin; Lilis - Satriah (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2018)
This study reveals the mental spiritual needs of patients, the patterns of Islamic spiritual counselors, and the results of Islamic spiritual guidance in five hospitals namely Yarsi Hospital in Pontianak, Yarsi Ibnu Sina Islamic Hospital in Padang, R. Syamsudin, SH Hospital in Sukabumi, Al-Ihsan Hospital in Baleendah, and Ujungberung Hospital, Bandung. This research formulated da'wah bi al-Irsyad model that can maintain the spiritual mental health of patients in hospital. The results of this qualitative descriptive study with the Research and Development approach showed that the spiritual mental needs of patients in hospitals included: motivation to recover and be healthy, guidance in sickness, prayer in sick condition, nadza '(sakaratul maut) and positive assistance from patient's family. From the results of the study found constructs of bi al-Irsyād da'wah models in the form of general basic services, responsive services, individual planning services and system support services. This study recommends further research to develop more feasible and applicable models and need further collaboration between related parties to formulate policies in the maintenance of the patient's mental spiritual health. Penelitian ini mengungkapkan kebutuhan mental spiritual pasien rawat inap, pola kerja pembimbing rohani Islam, dan hasil dari bimbingan rohani Islam di lima rumah sakit yaitu Rumah Sakit Umum Yarsi Pontianak, Rumah Sakit Islam Yarsi Ibnu Sina Padang, Rumah Sakit Umum Daerah R. Syamsudin, SH Kota Sukabumi, Rumah Sakit Umum Daerah Al-Ihsan Baleendah, dan Rumah Sakit Umum Daerah Ujungberung Kota Bandung. Dari penelitian ini dirumuskan model dakwah bi al-Irsyād yang dapat memelihara kesehatan mental spiritual pasien rawat inap di rumah sakit. Hasil penelitian deskriptif kualitatif dengan pendekatan Reseach and Development ini menunjukkan bahwa kebutuhan mental spiritual pasien rawat inap di rumah sakit meliputi: motivasi untuk sembuh dan sehat, bimbingan dalam keadaan sakit, salat dalam keadaan sakit, nadza’ (sakaratul maut) dan pendampingan yang positif dari keluarga pasien. Dari hasil penelitian ditemukan konstruk model dakwah bi al-Irsyād berupa layanan dasar umum, layanan responsif, layanan perencanaan individual dan layanan dukungan sistem. Penelitian ini merekomendasikan penelitian lanjutan untuk mengembangkan model ke arah yang lebih feasible dan teruji, serta perlu kerjasama antar pihak terkait untuk merumuskan kebijakan dalam pemeliharaan kesehatan mental spiritual pasien.